Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemandirian Belajar Siswa Sekolah Dasar Mata Pelajaran IPA - Kusuma Wardani , Lintang; Lia Fatmawati; Berliana, Silvia; Heny Oktaviana; Erik Aditia Ismaya; Fina Fakhriyah (AIJER: Algazali International Journal Of Educational Research, 2023)
The purpose of this study was to analyze the effect of the problem-based learning model or the so-called Problem Based Learning learning model on student learning independence at the elementary school level in science subjects. The method used in this study is the SLR (System Literature Review) method. Data collection was carried out by documenting and reviewing all journal articles regarding student learning independence which had similar research in this research report. The articles used in this study were 14 journal articles obtained from Google Scholar with the help of the POP application, also known as publish or perish. Based on research, it is known that the use of problem-based learning models in elementary schools is able to increase student independence in learning, students can be more active and participate in the learning process so that they are able to solve problems. This shows that the problem-based learning model or the so-called problem-based learning model can have a positive effect on the learning process so that it can improve the science learning outcomes of elementary school students. The implications of this research are expected to be able to help educators or teachers to be able to choose the right application of learning models to influence student learning independence.